Fat intake impairs the recovery of endothelial function following mental stress in young healthy adults - Baynham, Rosalind; Weaver, Samuel R. C.; Rendeiro, Catarina; Veldhuijzen van Zanten, Jet J. C. S. (Frontiers in Nutrition, 2023)
Mental stress has been identified as a trigger of cardiovascular events. A single episode of stress can induce acute impairments in endothelial function in healthy adults. Importantly, during stressful periods, individuals often resort to unhealthy behaviours, such as increased consumption of high-fat foods, which is also known to negatively impact endothelial function. Therefore, this study examined whether consumption of a high-fat meal would further exacerbate the negative effect of mental stress on vascular function. In a randomised, counterbalanced, cross-over, postprandial intervention study, 21 healthy males and females ingested a high-fat (56.5g fat) or a low-fat (11.4g fat) meal 1.5 hours before an 8-minute mental stress task (Paced-Auditory-Serial-Addition-Task, PASAT). Plasma triglyceride (TAG) concentration was assessed pre-and post-meal. Forearm blood flow (FBF), blood pressure (BP), and cardiovascular activity were assessed pre-meal at rest and post-meal at rest and during stress. Endothelial function, measured by brachial flow-mediated dilatation (FMD) was assessed pre-meal and 30 and 90 minutes following mental stress. Plasma TAG concentration was significantly increased following the high-fat meal compared to the low-fat condition. Mental stress induced similar increases in peripheral vasodilation, BP, and cardiovascular activity, and impaired FMD 30 minutes post-stress, in both conditions. FMD remained significantly impaired 90 minutes following stress in the high-fat condition only, suggesting that consumption of fat attenuates the recovery of endothelial function following mental stress. Given the prevalence of fat consumption during stressful periods among young adults, these findings have important implications for dietary choices to protect the vasculature during periods of stress.